2007
DOI: 10.1073/pnas.0700206104
|View full text |Cite
|
Sign up to set email alerts
|

Extrachromosomal element capture and the evolution of multiple replication origins in archaeal chromosomes

Abstract: In all three domains of life, DNA replication begins at specialized loci termed replication origins. In bacteria, replication initiates from a single, clearly defined site. In contrast, eukaryotic organisms exploit a multitude of replication origins, dividing their genomes into an array of short contiguous units. Recently, the multiple replication origin paradigm has also been demonstrated within the archaeal domain of life, with the discovery that the hyperthermophilic archaeon Sulfolobus has three replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
108
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 29 publications
4
108
0
Order By: Relevance
“…The in vivo replication rates of S. solfataricus and S. acidocaldarius, both of which contain three replica- . The origin recognition boxes associated with the origins in these species (26,27) are also conserved in the S. tokodaii genome sequence (15), and it is therefore likely that this species also harbors three origins, resulting in a replication rate of around 70 bp/s. A. pernix has been shown to contain two origins (26), yielding an in vivo replication rate of 110 bp/s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo replication rates of S. solfataricus and S. acidocaldarius, both of which contain three replica- . The origin recognition boxes associated with the origins in these species (26,27) are also conserved in the S. tokodaii genome sequence (15), and it is therefore likely that this species also harbors three origins, resulting in a replication rate of around 70 bp/s. A. pernix has been shown to contain two origins (26), yielding an in vivo replication rate of 110 bp/s.…”
Section: Discussionmentioning
confidence: 99%
“…The origin recognition boxes associated with the origins in these species (26,27) are also conserved in the S. tokodaii genome sequence (15), and it is therefore likely that this species also harbors three origins, resulting in a replication rate of around 70 bp/s. A. pernix has been shown to contain two origins (26), yielding an in vivo replication rate of 110 bp/s. We have shown that flow cytometry is a convenient tool for genome size determination (4,21), even for the eukaryote Giardia lamblia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two-dimensional gel analysis of replicating molecules confirmed the location of the DNA replication origin near the orc1 gene of P. abyssi, with predicted origin binding sequences and AT-rich DNA unwinding elements nearby (18). An investigation of DNA replication in Aeropyrum pernix used a combination of biochemical and two-dimensional gel electrophoresis and identified two potential sites of replication initiation, on opposite sides of the circular genome (14,28). One of these sites (oriC1 Ap ) contained four origin recognition boxes and an AT-rich region and was shown to be bound by the ORC1 gene.…”
mentioning
confidence: 99%
“…One of these sites (oriC1 Ap ) contained four origin recognition boxes and an AT-rich region and was shown to be bound by the ORC1 gene. The other site (oriC2 Ap ) contained repeat elements without an intervening AT-rich region and has been shown by two-dimensional gel electrophoresis to contain an active replication origin (28). An examination of replication in two Sulfolobus spp., Sulfolobus solfataricus and Sulfolobus acidocaldarius (16,30), by use of a combination of bioinformatic and two-dimensional gel analysis and of marker frequency by use of DNA microarrays identified three well-separated replication origins per genome.…”
mentioning
confidence: 99%
“…Additionally, they are not easily manipulated. Typically, crenarchaeotes, like Sulfolobus, Aeropyrum, and Pyrobaculum species have multiple origins (24,(35)(36)(37). Euryarchaeota, however, have either one origin, like Pyrococcus and Archaeoglobus species (38,39), or multiple origins, like Methanocaldococcus (39), Halobacterium (5,40), and Haloferax (41) species.…”
Section: Discussionmentioning
confidence: 99%